Population genomics of the widespread African savannah trees Afzelia africana and Afzelia quanzensis reveals no significant past fragmentation of their distribution ranges - Donkpegan, A.S.L.; Piñeiro, R.; Heuertz, M.; Duminil, J.; Daïnou, K.; Doucet, J.-L.; Hardy, Olivier J. (Wiley, 2020)
Few studies have addressed the evolutionary history of tree species from African savannahs. Afzelia contains economically important timber species, including two species widely distributed in African savannahs: A. africana in the Sudanian region and A. quanzensis in the Zambezian region. We aimed to infer whether these species underwent range fragmentation and/or demographic changes, possibly reflecting how savannahs responded to Quaternary climate changes. We characterized the genetic diversity and structure of these species across their distribution ranges using nuclear microsatellites (SSRs) and genotyping‐by‐sequencing (GBS) markers. Six SSR loci were genotyped in 241 A. africana and 113 A. quanzensis individuals, while 2800 high‐quality single nucleotide polymorphisms (SNPs) were identified in 30 A. africana individuals. Both species appeared to be mainly outcrossing. The kinship between individuals decayed with the logarithm of the distance at similar rates across species and markers, leading to relatively small Sp statistics (0.0056 for SSR and 0.0054 for SNP in A. africana, 0.0075 for SSR in A. quanzensis). The patterns were consistent with isolation by distance expectations in the absence of large‐scale geographic gradients. Bayesian clustering of SSR genotypes did not detect genetic clusters within species. In contrast, SNP data resolved intraspecific genetic clusters in A. africana, illustrating the higher resolving power of GBS. However, these clusters revealed low levels of differentiation and no clear geographical entities, so that they were interpreted as resulting from the isolation by distance pattern rather than from past population fragmentation. These results suggest that populations have remained connected throughout the large, continuous savannah landscapes. The absence of clear phylogeographic discontinuities, also found in a few other African savannah trees, indicates that their distribution ranges have not been significantly fragmented during the climatic oscillations of the Pleistocene, in contrast to patterns commonly found in African rainforest trees.